Effect of slope, aspect, and position on soil properties at various depths in an oil palm plantation in Selangor, Malaysia - OMAR MOHAMED IBRAHIMI ABDALRAHEM; MOHD HASMADI ISMAIL; PAKHRIAZAD HASSAN ZAKI; DALJIT SINGH A/L KARAM SINGH (Society for Indonesian Biodiversity, 2024)
Abstract. Abdalrahem OMI, Ismail MH, Zaki PH, Singh DSAK. 2024. Effect of slope, aspect, and position on soil properties at various depths in an oil palm plantation in Selangor, Malaysia. Biodiversitas 25: 2507-2514. Limited information exists regarding the study of land and topographic characteristics and their influence on palm oil yield, as well as the effects on the physio-chemical properties of the soil. This study examined the impact of slope, aspect, and position at different soil depths on the physical and chemical properties of an oil palm (Elaeis guineensis Jacq.) plantation in an oil palm plantation in Selangor, Malaysia. Two sites with distinct north and south aspects were chosen for each slope site. Three equal positions were identified within each slope: Summit, Sideslope, and Toeslope. Random sampling determined soil physical and chemical properties at two depths (0-20 cm, 20-40 cm). This study analyzed soil chemical properties, including pH, EC, total N, P, Ext K, Ca, Mg, and soil texture, and the soil properties across different slope positions, depths, and aspects results indicated a significant difference (p<0.05). The soil properties' main factors contributing to the observed variations were slope position and soil depth. Slope position had a significant effect (p<0.05) on soil pH, EC, Ca, Mg, K, and N. Soil depth significantly influenced (p<0.05) all soil properties examined. The slope aspect also significantly affected (p<0.05) pH, Ca, Mg, and K. The soil texture classification ranged from sandy clay to sandy clay loam. Sand constituted the highest proportion of soil particles in both aspect slopes, followed by clay. The clay content increased with depth, specifically in the 20-40 cm range.